Człowiek we współczesnych koncepcjach i metodach zarządzania - Trenkner, Małgorzata (People in Modern Management Concepts and Methods, 2008)
The purpose of this article is to identify research problems concerning human factor in modern management concepts and methods. The paper presents postulates for including human factor in the process of selection, implementation and realization of various management concepts and methods. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 34, s. 71-77